Computational and analytical measurement of air-fuel mixture uniformity and alternative fuels' ignition delay in ICEs. (February 2021) - Taghavifar, Hadi; Khalilarya, Shahram; Jafarmadar, Samad
Abstract: Mixing dynamics is a crucial factor for the combustion of fuels in thermal systems such as boilers, rockets, engines, etc. The quality of the mixture is determinate for controlling the ignition and kinetics dynamics progress during premixed and diffusion phases affecting energy conversion and ultimate emission species proliferation in DI diesel engines. In this regard, quantifying the mixture quality computationally in CFD framework and fuel distribution in cells can be a forwarding step in accurate measurement of within-cylinder parameters such as equivalence ratio, pressure, IMEP, thermal efficiency, and emission concentration. This study, in particular, proposes a novel analytical approach based on Heter F(θ) and stoichiometric air/fuel ratio AFRst, and statistical means to obtain an accurate parameter for uniformity of mixture in the cylinder. The new parameter for measuring the mixture quality is based on the standard deviation of the ideal mixture formed in the combustion chamber. The parameter is then used for mathematical ignition delay (ID) modeling for various fuels of diesel, DME, and n-heptane. The conventional models have customarily applied mean pressure (as in Watson model, 1980) or both pressure and equivalence ration (as Assanis, 2003) to compute the ignition delay. However, in this work pressure and modified HF (HF∗) are taken into account which demonstrates 18.3% error reduction with that of Watson and 8.3% reduction for Assanis model when compared to experimental results for diesel-powered engine. The obtained results show a significant agreement of experimental and modeling data for the engine speed ranging 1500–4000 rpm for various fuels of diesel, n-heptane, and DME. The implication of the results encompasses a wide range of application from direct use in industry to UDF and incorporation in software to thermodynamic analysis of energy devices. Highlights : A new parameter for air-fuel distribution is introduced, a better uniformity index. Proposal of an ignition delay correlation based on modified homogeneity factor. Up to 8.3% error reduction of ignition delay with proposed correlation for diesel. The predicted ignition delay trend conforms with viscosity and cetane number for DME and n-heptane.